Thermo-elastic-plastic processes with finite deformations - Rogovoy, Anatoliy Alekseevich (Computational Continuum Mechanics, 2013)
In this paper, thermo-elastic-plastic processes are described using author's approach, which is based on the superposition of small deformations on the finite ones. This allows us to construct models of complex media in the framework of finite deformations taking into account the peculiarities of their thermo-elastic-plastic behavior including structural changes occurring in the material.
Keywords: thermo-elastic-plastic; kinematics; constitutive relations; thermodynamics; structural changes